Baseline kidney function and the effects of dapagliflozin on health status in heart failure in DEFINE‐HF and PRESERVED‐HF - Andrew P. Ambrosy; Andrew J. Sauer; Shachi Patel; Sheryl L. Windsor; Barry A. Borlaug; Mansoor Husain; Silvio E. Inzucchi; Dalane W. Kitzman; Darren K. McGuire; Sanjiv J. Shah; Kavita Sharma; Guillermo Umpierrez; et al. (ESC Heart Failure)
Abstract Aims Sodium–glucose co‐transporter‐2 (SGLT2) inhibitors improve health status and outcomes in the setting of heart failure (HF) across the range of ejection fraction (EF). Baseline kidney disease is common in HF, complicates HF management and is strongly linked to worse health status. This study aimed to assess whether the treatment effects of dapagliflozin on health status vary based on estimated glomerular filtration rate (eGFR). Methods and Results We conducted a pooled participant‐level analysis of two double‐blind, randomized trials, DEFINE‐HF (n = 236) and PRESERVED‐HF (n = 324), which evaluated dapagliflozin versus placebo. Both multicentre studies enrolled adults with HF, New York Heart Association Class II or higher, elevated natriuretic peptides, and an EF < 40% in DEFINE‐HF or >45% in PRESERVED‐HF. The primary exposure was eGFR. The main outcome was the Kansas City Cardiomyopathy Questionnaire Clinical Summary Score (KCCQ‐CSS) at 12 weeks. Across both trials, there were 583 (99.3%) participants with a baseline eGFR. The median (25th, 75th) eGFR was 59 (46, 77) mL/min/1.73 m2. Dapagliflozin improved KCCQ‐CSS at 12 weeks [placebo‐adjusted difference, +5.0 points, 95% confidence interval (CI) 2.6–7.5; P < 0.001], and this was consistent in participants with an eGFR ≥ 60 (+6.0 points, 95% CI 2.4–9.7; P = 0.001) and eGFR < 60 (+4.1 points, 95% CI 0.5–7.7; P = 0.025) (P interaction = 0.46). The benefits of dapagliflozin on KCCQ‐CSS remained robust across eGFR when modelled as a continuous variable (P interaction = 0.48). Conclusions Dapagliflozin led to early and clinically meaningful improvements in health status in HF patients, regardless of EF or baseline eGFR.